Risk of myocardial infarction and stroke following microbiologically confirmed urinary tract infection: a self-controlled case series study using linked electronic health data - Ashley Akbari; David Gillespie; Fiona V Lugg-Widger; Rebecca Cannings-John; Kathryn Hughes; Nicola F Reeve; Haroon Ahmed; Fatemeh Torabi; Mandy Wootton; Victoria Best (BMJ Open)
Objectives The inflammatory response from acute infection may trigger cardiovascular events. We aimed to estimate associations between microbiologically confirmed urinary tract infections (UTIs) and first acute myocardial infarction (MI) and stroke.Design We used a self-controlled case series, with risk periods 1–7, 8–14, 15–28 and 29–90 days after UTI. Included individuals experienced the outcome and exposure of interest and acted as their own controls.Setting We used individually linked general practice, hospital admission and microbiology data for the population of Wales held by the Secure Anonymised Information Linkage databank.Participants Included individuals were Welsh residents aged over 30 years with a record of a hospital admission for MI or stroke (outcomes) and evidence of a microbiologically confirmed UTI (exposure) during the study period of 1 January 2010 to 31 December 2020.Main outcome measures The primary outcome was acute MI or stroke identified using the International Classification of Disease V.10 codes from inpatient diagnoses recorded in the Patient Episode Database for Wales. We used Poisson regression to estimate incidence rate ratios (IRRs) and 95% CIs for MI and stroke during predefined risk periods, compared with baseline periods.Results During the study period, 51 660 individuals had a hospital admission for MI, of whom 2320 (4.5%) had 3900 microbiologically confirmed UTIs, and 58 150 had a hospital admission for stroke, of whom 2840 (4.9%) had 4600 microbiologically confirmed UTIs. There were 120 MIs during risk periods and 2190 during baseline periods, with an increased risk of MI for 1–7 days following UTI (IRR 2.49, 95% CI (1.65 to 3.77)). There were 200 strokes during risk periods and 2640 during baseline periods, with an increased risk of stroke for 1–7 days following UTI (IRR 2.34, 95% CI (1.61 to 3.40)).Conclusions UTI may be a trigger for MI or stroke. Further work is needed to understand mechanisms and test interventions to reduce the risk of cardiovascular events among people with UTIs in primary care.